دور المراجعة المشتركة في تحسين الخصائص النوعية للمعلومات المحاسبية الواردة في القوائم المالية في المصارف التجارية الليبية: دراسة ميدانية من وجهة نظر المراجعين الخارجيين والأكاديميين بالمنطقة الشرقية - عبدالقادر العريبي خالد; فرج الطيرة مروة (Dirasat in Economics and Business, 2026)
This study aims to identify the role of joint auditing in enhancing the qualitative characteristics of accounting information presented in the financial statements of Libyan commercial banks. The study addressed five main dimensions: relevance, reliability, comparability, verifiability, and consistency. The study adopted a descriptive-analytical methodology and collected data through a questionnaire distributed to a sample of 180 individuals, comprising financial managers, accountants, internal auditors in commercial banks, auditors from the Audit Bureau, and external auditors registered with the Central Bank of Libya. Appropriate statistical methods were used to analyze the data through the SPSS program. The study tested the main hypothesis: “Joint auditing plays a role in enhancing the qualitative characteristics of accounting information in the financial statements of Libyan commercial banks.” From this main hypothesis, five sub-hypotheses were derived. The findings of the study indicate that joint auditing plays an effective role in improving all dimensions of the qualitative characteristics of accounting information in the financial statements of Libyan commercial banks. The study recommends adopting a joint audit system in Libyan banks due to its positive impact on enhancing the quality of accounting information. Furthermore, the study emphasized the importance of strengthening coordination between regulatory and accounting bodies in the country to establish a clear regulatory framework that governs the work of joint auditors and minimizes potential conflicts. It also called for incorporating the concept of joint auditing into academic curricula within accounting departments to raise early awareness among students about its importance.